Breast cancer awareness's and attitude among regular health-care users versus irregular in a sample of Kurdish women in the west of Iran - Zahra Rastad; Marzieh Kaboudi; Nematollah Shiri (Wolters Kluwer Medknow Publications, 2021)
INTRODUCTION: It is universally acknowledged that strengthen the participation rate in breast cancer (BC) screening can find cancer in its earlier stages. The aim of this study was to determine the effect of regular visits to the health centers on women's knowledge and attitude about BC screening. MATERIALS AND METHODS: In a cross-sectional study, data were collected from 380 women identified with Kurdish background, who were registered in health care centers of Islamabad-e Gharb during January and February 2017. The subjects were divided into two regular and irregular groups based on the quantity of presence in health centers. Data on women's awareness and attitude about BC screening were collected by a trained interviewer using a structured questionnaire. Bivariate analysis, analysis of variance, and independent sample t-test were used to see the mean differences within the groups. The level of confidence was set at 0.05 significant. RESULTS: Women were representative of four health-care centers of the city, mainly ≤39 years old (73.9%), married (96.3%), with high school education (44.2%) characteristics. The total mean ± standard deviation of awareness score about BC was 6.03 ± 3.90. In total, 19.2% of participants had poor (<2.13), 64.2% had an average (2.13-9.93), and 16.6% had good (>9.93) awareness about BC. The results showed that the level of knowledge and attitude about BC screening was significantly different between regular and irregular groups (P < 0.05). CONCLUSION: An important message from this study is the need for improved and coordinated BC education for all social classes of women. It is necessary to discover ways to encourage women with academic education to visit health centers regularly during interventional studies.